Association of feeding practices and immunization with nutritional status of infants in jasra block of Allahabad district - Mishra, Mili; Singh, Richa; Dwivedi, S; Hassan, M A; Parveen, K; Khan, M A (Indian Journal of Child Health, 2015)
Objective: The objective was to find the association of feeding practices and immunization with nutritional status of infants in Jasra Block of Allahabad district. Materials and Methods: A cohort study was conducted in a rural community among infants born during the period of November 2011 to April 2012. Information, Education and Counselling was given to their mothers starting from last 3 months of pregnancy and continued till the newborns completed 1-year of age. Then feeding practices, immunization, and nutritional status (in terms of weight for age) was assessed. Results: About 56.25% infants were exclusively breastfed and 53.75% infants were timely started on complementary feeding. 87.5% infants were fully immunized and the rest 12.5% were partially immunized. Growth of more than half of the infants, i.e., 47 (60%) followed a normal growth curve and weight of 33 (40%) infants was below 2 standard deviation. There was no significant difference between the mean weight at birth (i.e., 2.56 kg for infants with adequate feeding and immunization practices and 2.51 kg for infants with inadequate immunization and feeding practices). On the other hand, difference in the mean weight among two groups at 3, 6, and 9 months was statistically significant. Conclusion: Feeding practices and immunization have an association with nutritional status of infants in terms of better weight for age.